Freezing Medium Containing 5% DMSO Enhances the Cell Viability and Recovery Rate After Cryopreservation of Regulatory T Cell Products ex vivo and in vivo - Kaiser, Daniel; Otto, Natalie Maureen; McCallion, Oliver; Hoffmann, Henrike; Zarrinrad, Ghazaleh; Stein, Maik; Beier, Carola; Matz, Isabell; Herschel, Marleen; Hester, Joanna; Moll, Guido; Issa, Fadi; et al. (Frontiers in Cell and Developmental Biology, 2021)
Cell therapies have significant therapeutic potential in diverse fields including regenerative medicine, transplantation tolerance, and autoimmunity. Within these fields, regulatory T cells (Treg) have been deployed to ameliorate aberrant immune responses with great success. However, translation of the cryopreservation strategies employed for other cell therapy products, such as effector T cell therapies, to Treg therapies has been challenging. The lack of an optimized cryopreservation strategy for Treg products presents a substantial obstacle to their broader application, particularly as administration of fresh cells limits the window available for sterility and functional assessment. In this study, we aimed to develop an optimized cryopreservation strategy for our CD4+CD25+Foxp3+ Treg clinical product. We investigate the effect of synthetic or organic cryoprotectants including different concentrations of DMSO on Treg recovery, viability, phenotype, cytokine production, suppressive capacity and in vivo survival following GMP-compliant manufacture. We additionally assess the effect of adding the extracellular cryoprotectant polyethylene glycol (PEG), or priming cellular expression of heat shock proteins as strategies to improve viability. We find that cryopreservation in serum-free freezing medium supplemented with 10% human serum albumin and 5% DMSO facilitates improved Treg recovery and functionality and supports a reduced DMSO concentration in Treg cryopreservation protocols. This strategy may be easily incorporated into clinical manufacture protocols for future studies.